Standing Our Ground : Women, Environmental Justice, and the Fight to End Mountaintop Removal - Barry, Joyce M. (Book collections on Project MUSE., 2012)
Standing Our Ground: Women, Environmental Justice, and the Fight to End Mountaintop Removal examines women's efforts to end mountaintop removal coal mining in West Virginia. Mountaintop removal coal mining, which involves demolishing the tops of hills and mountains to provide access to coal seams, is one of the most significant environmental threats in Appalachia, where it is most commonly practiced. The Appalachian women featured in Barry's book have firsthand experience with the negative impacts of Big Coal in West Virginia. Through their work in organizations such as th.